Kedudukan Hukum Pengelolaan Tanah Wakaf oleh Nazhir di Kecamatan Dungingi Kota Gorontalo - Marwan Marwan; Nur Insani (Al-'Aqdu: Journal of Islamic Economics Law, 2022)
The aim of this study is to know and to analyze the role of Nazhir in managing the waqf land according to it purpose in the district of Dungingi, Gorontalo City. The result of the study shows that the role of Nazhir in managing the waqf land in the district of Dungingi, Gorontalo City is not maximal yet. This can be seen from the existence of some waqf lands that don’t have a certificate of ownership. Additionally, it only becomes as a place of worship not as a productive waqf.